News Frames of Soft Power in US Foreign Policy Through electronic press Service: News Link for U.S. Embassy & Consulates Website in Iraq (Sample) - Al-Musawi, Hayder Ghazi Hussein (Al-Adab Journal, 2021)
With its messages and content, media has become an effective force and an essential tool of foreign policies as the digital revolution and communication and telecommunication technology offered a momentum that amplified the capabilities of those means to achieve a great deal of harmony and coordination between the aims of the foreign policies of the governments and their goals. This is done by providing a framework to the communicative content expressing its position on the events and events which is in line with such objectives and goals in a gentle diplomatic manner. This inspired the idea of studying the news contents on the websites of the US Embassy and consulates in Iraq to express the US Government position on specific issues and events. The US Embassy did not present its positions in an objective, abstract manner; rather, it delivered news content that expressed specific positions on issues and events within specific frameworks: humanitarian frameworks, consequences and ramifications frameworks, values and morals frameworks, and responsibility frameworks.